Worklife balance and organisational commitment of secondary school teachers in Kubang Pasu District - Zuhaida, Abdullah (2013)
This study was conducted to gain view on the issues of work life balance and organizational commitment among secondary school teachers servicing in Kubang Pasu District. The main purpose of this study is to determine the relationship between work life balance and organizational commitment. Besides, this study also aims to determine the level of whether work life balance and which dimension is the most dominant dimension impacting the teachers. Three dimensions of work life balance, namely personal life inteference with work (PLIW), work interference with personal life (WIPL) and work/personal life enhancement (WPLE) are involved in the study as the independent variables while organizational commitment is the dependent variable. This study was conducted through quantitative method where data is collected using questionnaires. Survey questionnaires were used in obtaining feedback from respondents. Samples of the research were secondary school teachers in Kubang Pasu District in Kedah State involving a total of 255 respondents chosen from simple random sampling. A 46 item questionnaire using a 5 point time relate scale was used to measure work life balance while a 17 item questionaire was used to measure organizational commitment. The survey response was analyzed by using the Statistical Package for Social Sciences (SPSS) Version 16.0. Frequencies and percentage statistics were computed and Pearson Correlation coefficient was also carried out. The findings show that work/personal life enhancement is the most-dominant dimension among the respondents, suggesting that the respondents perceive neither work interfere their personal life nor vice versa, and that there is a significant relationship between work life balance and their organisational commitment. For future research, it is suggested that the scope of the study be widen from the current study